Enhancing and Extending Biological Performance and Resilience - Rehana K. Leak; Edward J. Calabrese; Walter J. Kozumbo; Jeffrey M. Gidday; Thomas E. Johnson; James R. Mitchell; C. Keith Ozaki; Reinhard Wetzker; Aalt Bast; Regina G. Belz; Hans E. Bøtker; Sebastian Koch; et al. (SAGE Publishing, 2018)
Human performance, endurance, and resilience have biological limits that are genetically and epigenetically predetermined but perhaps not yet optimized. There are few systematic, rigorous studies on how to raise these limits and reach the true maxima. Achieving this goal might accelerate translation of the theoretical concepts of conditioning, hormesis, and stress adaptation into technological advancements. In 2017, an Air Force-sponsored conference was held at the University of Massachusetts for discipline experts to display data showing that the amplitude and duration of biological performance might be magnified and to discuss whether there might be harmful consequences of exceeding typical maxima. The charge of the workshop was "to examine and discuss and, if possible, recommend approaches to control and exploit endogenous defense mechanisms to enhance the structure and function of biological tissues." The goal of this white paper is to fulfill and extend this workshop charge. First, a few of the established methods to exploit endogenous defense mechanisms are described, based on workshop presentations. Next, the white paper accomplishes the following goals to provide: (1) synthesis and critical analysis of concepts across some of the published work on endogenous defenses, (2) generation of new ideas on augmenting biological performance and resilience, and (3) specific recommendations for researchers to not only examine a wider range of stimulus doses but to also systematically modify the temporal dimension in stimulus inputs (timing, number, frequency, and duration of exposures) and in measurement outputs (interval until assay end point, and lifespan). Thus, a path forward is proposed for researchers hoping to optimize protocols that support human health and longevity, whether in civilians, soldiers, athletes, or the elderly patients. The long-term goal of these specific recommendations is to accelerate the discovery of practical methods to conquer what were once considered intractable constraints on performance maxima.